THE DIABETES BURDEN IN INDIA AND THE NUTRITIONAL PROMISE OF MILLETS IN ITS PREVENTION AND CONTROL - Kaur, Jaspreet (ShodhKosh: Journal of Visual and Performing Arts, 2022)
India is witnessing a significant rise in the prevalence of diabetes mellitus, particularly type 2 diabetes, across various age groups and genders. This surge is accompanied by an increase in diabetes-related complications, including cardiovascular diseases, neuropathy, nephropathy, and retinopathy, which contribute to heightened morbidity and mortality. Many researchers have highlighted the potential role of millets, a group of small-seeded grains, in the prevention and management of diabetes and its complications. Millets are rich in dietary fiber, have a low glycemic index, and contain bioactive compounds that may aid in glucose metabolism and insulin sensitivity. This review is an attempt to review findings from national and international studies to provide a comprehensive understanding of diabetes prevalence across different demographics in India, the common complications associated with the disease, and the role of millets in its prevention and management.